Accounting for the Effects of Oil Prices on Exchange Rate in Nigeria: Empirical Evidence from Linear and Non-Linear ARDL Models - NI. Nasir; S. Sa’ad; A.S. Rafindadi; Ali Baba Usman (European Scientific Journal, ESJ, 2023)
This study empirically examines the impact oil prices on the exchange rate in Nigeria. Time series annual dataset spanning 1980 to 2018 was estimated using the linear and nonlinear ARDL model developed by Pesaran and Shin, (1998) & Pesaran, et al. (2001) and Shin, et al. (2014); where oil prices, nominal exchange rate, interest rate, and oil revenue serves as the variables for analysis.  From the result of the linear-ARDL models  both the long run and short-run revealed that oil price has positive and significant impact on exchange rate. Similarly, the nonlinear model also revealed that in both the long run and the short-run, both the rising and falling oil prices have an increasing impact on exchange rate. Policy implication for the findings suggests that, the authority should hold the exchange rate constant during a stable period of oil prices in order to exert pressure on the foreign currency so that the oil prices will continue to have increasing impact on exchange rate as it was during the rising and falling periods.